2001
DOI: 10.1034/j.1399-0012.2001.150306.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous mycophenolate mofetil after allogeneic blood stem cell transplantation

Abstract: The application of i.v. MMF is safe at a weight-adjusted dose between 25 and 34 mg/kg after allogeneic BSCT. The measured trough blood levels of MPA in patients after BSCT were ten times lower than in healthy volunteers. The toxicity induced by the conditioning therapy seems to negatively influence the pharmacokinetic behavior of MMF, MPA and MPAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 18 publications
1
30
1
Order By: Relevance
“…Third, we saw no apparent additional anti-GVHD prophylactic activity with adjunctive MMF. 69,73 Finally, the rapid engraftment dynamic, relatively early achievement of full donor chimerism and potent GVL effects presumably delivered soon after transplant, appears to support such a concept. 44 A minimal intensity HCT allotransplant approach might then be considered an attractive therapeutic option for those of advancing age with AML/MDS and either an HLA MRD or MUD.…”
Section: Discussionmentioning
confidence: 87%
“…Third, we saw no apparent additional anti-GVHD prophylactic activity with adjunctive MMF. 69,73 Finally, the rapid engraftment dynamic, relatively early achievement of full donor chimerism and potent GVL effects presumably delivered soon after transplant, appears to support such a concept. 44 A minimal intensity HCT allotransplant approach might then be considered an attractive therapeutic option for those of advancing age with AML/MDS and either an HLA MRD or MUD.…”
Section: Discussionmentioning
confidence: 87%
“…22,23 Studies on the use of MMF as part of GVHD prophylaxis have been limited in size and mostly inconclusive, as most investigators reported insufficient plasma levels of the active metabolite MPA. [3][4][5]8,24,25 Most of these studies revealed a favorable toxicity profile of combinations of MMF with calcineurin inhibitors compared to regimens incorporating MTX. Encouraging results were reported by Nash et al, 7 who demonstrated that the rate of GVHD Targeting mycophenolate mofetil for GVHD prophylaxis I Haentzschel et al after transplantation from matched-sibling donors could be significantly reduced by using higher MMF doses up to 60 mg/kg daily.…”
Section: Discussionmentioning
confidence: 99%
“…administration in combination with CsA as GVHD prophylaxis after allogeneic blood SCT from HLAcompatible related and unrelated donors. 3,8 No severe side effects and adverse events were observed. Compared to a control group receiving MTX and CsA, we saw no significant differences in the mucosal and intestinal toxicities and in the incidence of acute GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…6 This resulted in MPA concentrations below the therapeutic range recommended for SOT. 7 Furthermore, correlations of MPA plasma concentrations at steady state and AUC with degree of T-cell chimerism 8 and incidence of graft rejection 6,8 have been suggested.…”
Section: Introductionmentioning
confidence: 99%